Factores psicológicos que influyen en la preparación deportiva en atletas de 800 metros, categoría prejuvenil, en la Federación Deportiva Provincial de Loja, 2024 - Chamba Herrera, Eddy Paul (2024)
This Curricular Integration Work was developed with the aim of analyzing the relationship between psychological factors and sports preparation in athletes of 800 meters, pre-youth category, in the Provincial Sports Federation of Loja (Federación Deportiva Provincial de Loja), 2024. This investigation included a mixed study, of a descriptive and correlational type with a quasi-experimental design. Butt's Sports Motives Test and State-Trait Anxiety Inventory (STAI) Test were applied as diagnostic instruments to a sample of 5 athletes. In the initial application, -19 points were obtained, indicating low motivation in Butt's Sports Motives Test. On the other hand, in the (STAI) in the Anxiety State (A/E) during the initial application a punctuation of 63 was found in women, and 38 in men, which indicates that the level of anxiety is high. Additionally, in the Trait Anxiety (A/R) in women 21 marks were attained and 3 in men, the level is low in this initial implementation. Having obtained these outcomes, a plan for the improvement of psychological factors was designed and structured in 9 sessions. Finally, some instruments were used, for example an evaluation, with the following marks: in the first test, 8 points evidenced low motivation, but with a reduction of 11 points. In the STAI, in State Anxiety (A/E) women obtained 58 points, which indicates that it remains at the high anxiety level, but with a decrease of points. On the other hand, in men, it remains at the same level; in Trait Anxiety (A/R) in both women and men the level is low after the execution of the improvement plan, which shows that the levels were maintained and not augmented. It is concluded that once the upgrading plan was applied, there was a rise in points in motivation, but regarding anxiety, the values were maintained and did not increase, which shows, the improvement plan focused on psychological factors had positive effects. Keywords: Motivation, anxiety, Sports Psychology, behavior